The Impact of Food Bioactives on Health In Vitro and Ex Vivo Models - Verhoeckx, Kitty; Cotter, Paul; López-Expósito, Iván; Kleiveland, Charlotte; Lea, Tor; Mackie, Alan; Requena, Teresa; Swiatecka, Dominika; Wichers, Harry (Springer Nature, 2015)
Food Microbiology; Food Science; Human Physiology